Canonical Transient Receptor Potential (TRPC) Channels in Nociception and Pathological Pain - Sun, Zhi-Chuan (Neural Plast, 2020)
Chronic pathological pain is one of the most intractable clinical problems faced by clinicians and can be devastating for patients. Despite much progress we have made in understanding chronic pain in the last decades, its underlying mechanisms remain elusive. It is assumed that abnormal increase of calcium levels in the cells is a key determinant in the transition from acute to chronic pain. Exploring molecular players mediating Ca(2+) entry into cells and molecular mechanisms underlying activity-dependent changes in Ca(2+) signaling in the somatosensory pain pathway is therefore helpful towards understanding the development of chronic, pathological pain. Canonical transient receptor potential (TRPC) channels form a subfamily of nonselective cation channels, which permit the permeability of Ca(2+) and Na+ into the cells. Initiation of Ca(2+) entry pathways by these channels triggers the development of many physiological and pathological functions. In this review, we will focus on the functional implication of TRPC channels in nociception with the elucidation of their role in the detection of external stimuli and nociceptive hypersensitivity.